Peningkatan Kompetensi Juru Buku Guna Meningkatkan Kinerja Koperasi Melalui Sumber Daya Manusia Profesional - Suhartono (PT. Karya Inovatif Nusantara, 2024)
The word Cooperative comes from the English Cooperative which means Cooperation. So the definition of a cooperative is simply an organization or association of people who join voluntarily and have the same goal in meeting the needs and mutual cooperation. The quality of human resources is the key to the successful development of the cooperative movement in Indonesia. Improving the quality of human resources is reflected in the work competence and professionalism of the workforce. In today's world, workers are required to be able to work professionally. Workers are no exception such as Bookkeepers are also required to work professionally. To prove professionalism in their work or also often referred to as competent workers, the State has formed an institution or agency called the National Professional Certification Agency (BNSP). This institution has the right to issue a certificate to someone who has passed the test and is declared competent in a particular field. Competent and professional workers can be shown to increase knowledge, skills and work attitudes.